Cardiovascular Safety and Benefits of Semaglutide in Patients With Type 2 Diabetes: Findings From SUSTAIN 6 and PIONEER 6 - Nauck, Michael A.; Quast, Daniel R. (Frontiers in Endocrinology, 2021)
To exclude an excess risk of cardiovascular (CV) events, CV outcomes trials (CVOTs) have assessed the effects of new glucose-lowering therapies, including glucagon-like peptide-1 receptor agonists (GLP-1RAs), in patients with type 2 diabetes and established CV disease or CV risk factors. The CV safety of semaglutide vs. placebo, when added to standard care, was evaluated in the SUSTAIN 6 trial for the formulation administered once-weekly subcutaneously and in PIONEER 6 for the new once-daily oral formulation. In SUSTAIN 6 and PIONEER 6, both powered to demonstrate noninferiority (upper 95% confidence interval [CI] of the hazard ratio [HR] <1.8), there were fewer first major adverse CV events with semaglutide vs. placebo, with HRs of 0.74 (95% CI 0.58–0.95) and 0.79 (0.57–1.11), respectively. In SUSTAIN 6, the results were significant for noninferiority and superiority, although the latter was not prespecified. Surprisingly, CV and all-cause mortality were significantly reduced by oral semaglutide in PIONEER 6. The ongoing SOUL CVOT will further inform about CV outcomes with oral semaglutide vs. placebo (NCT03914326). Findings from SUSTAIN 6 and PIONEER 6 fall within the spectrum reported with other GLP-1RA CVOTs: noninferiority vs. placebo for major CV events was seen with lixisenatide and exenatide extended-release, while superiority was demonstrated with liraglutide, albiglutide, and dulaglutide. Beneficial outcomes have been recognized in international guidelines, which recommend subcutaneous liraglutide, semaglutide, and dulaglutide to reduce the risk of CV events in high-risk patients. Both indirect mechanisms via risk factor modification and direct effects via GLP-1 receptors in the CV system have been proposed to be responsible for CV event reductions. The exact mechanism(s) remains to be characterized, but appears to be mainly linked to anti-atherosclerotic effects. Further research is needed to elucidate the relevant mechanisms for CV benefits of GLP-1RAs.